Preparation method of aerogel composite and aerogel composite
Patent Information
- Application Number
- CN202611432439.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本申请的主要目的是提出一种气凝胶复合材料的制备方法及气凝胶复合材料,旨在解决如何规避纯二氧化硅气凝胶在较高温度下由于其燃烧热解而带来的潜在火灾风险,同时使其保持低密度、低热导率、高孔隙率和高比表面积等优异的基本特性,促进二氧化硅气凝胶复合材料在高温隔热领域的推广应用
[0016]本申请公开了一种气凝胶复合材料的制备方法,所述气凝胶复合材料利用二氧化钛作为遮光剂,可以对红外辐射传热起到抑制作用,降低气凝胶在高温下的热导率,进而降低其燃烧热值,从而规避纯二氧化硅气凝胶在较高温度下由于其燃烧热解而带来的潜在火灾风险,同时使其保持低密度、低热导率、高孔隙率和高比表面积等优异的基本特性,促进二氧化硅气凝胶复合材料在高温隔热领域的推广应用。
Smart Images

Figure CN123003255A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of aerogel composite materials, specifically to a method for preparing an aerogel composite material and the aerogel composite material itself. Background Technology
[0002] In the atmospheric pressure drying process of silica aerogel, introducing hydrophobic organic groups onto the aerogel surface can reduce capillary tension during drying, thereby reducing volume shrinkage caused by framework collapse. Simultaneously, the excellent hydrophobicity provided to the aerogel ensures its long-term effectiveness during use and allows it to fully utilize its thermal insulation properties.
[0003] However, at higher temperatures (200~500℃), the pyrolysis of organic groups in silica aerogels can destroy their structural integrity, causing the skeleton to collapse and shrink. At the same time, at even higher temperatures (500~1000℃), the high infrared transparency of silica aerogels enhances their infrared radiation heat transfer at high temperatures, increasing the high-temperature thermal conductivity of the aerogels and bringing unnecessary potential thermal hazards. Therefore, the combustion pyrolysis of silica aerogels at high temperatures has become a crucial issue and challenge in their application. Summary of the Invention
[0004] The main purpose of this application is to propose a method for preparing aerogel composite materials and the aerogel composite materials themselves. The aim is to solve the problem of how to avoid the potential fire risk caused by the combustion and pyrolysis of pure silica aerogel at high temperatures, while maintaining its excellent basic properties such as low density, low thermal conductivity, high porosity and high specific surface area, so as to promote the application of silica aerogel composite materials in the field of high temperature insulation.
[0005] In view of this, the present invention provides a method for preparing an aerogel composite material, comprising the following steps: S10. Mix and dilute the silicon source with the aqueous solution to obtain a diluted solution; S20. The diluted solution is mixed with the first acidic solution and subjected to acidification treatment to obtain a sol solution; S30. The sol solution is stirred and mixed with TiO2 powder, and then subjected to ultrasonic treatment to obtain a TiO2 / SiO2 mixed sol solution; S40. The TiO2 / SiO2 mixed sol solution is subjected to gelation treatment and aging to obtain TiO2 / SiO2 wet gel composite material. S50. The TiO2 / SiO2 wet gel composite material is mixed with a second acidic solution, solvent replacement is performed, surface modification treatment is carried out, and then it is dried to obtain an aerogel composite material.
[0006] In some embodiments, in step S10, the silicon source includes an organosilicon source and an inorganic silicon source. The organosilicon source includes tetraethyl orthosilicate, tetramethyl orthosilicate, tetrabutyl orthosilicate, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, polysiloxane, 3-[2-(2-aminoethylamino)ethylamino]propyltrimethoxysilane, and n-octyltriethoxysilane. The inorganic silicon source includes one or more of water glass and silicon tetrachloride; and / or, The alcohol solution includes one or more of methanol, ethanol, propanol, isopropanol, butanol, isobutanol, ethylene glycol, propylene glycol, diethylene glycol, butanediol, diacetone alcohol, glycerol, and diethylene glycol.
[0007] In some embodiments, in step S20, the first acidic solution includes one or more of hydrochloric acid, hydrofluoric acid, hydrobromic acid, sulfuric acid, phosphoric acid, nitric acid, oxalic acid, and glacial acetic acid; and / or, The concentration of the first acidic solution is 0.01~29.8 mol / L; and / or, The acidification treatment temperature is 10~70℃; and / or, The acidification treatment time is 0.1~50 min.
[0008] In some embodiments, in step S20, the volume ratio of the diluent to the first acidic solution is (1~24):1.
[0009] In some embodiments, in step S30, the solute in the alkaline aqueous solution includes one or more of ammonia, sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium carbonate, or sodium silicate; and / or, The concentration of the alkaline aqueous solution is 0.01~8 mol / L.
[0010] In some embodiments, in step S40, the average particle size of the TiO2 powder ranges from 0.1 to 3 μm; and / or, The mass of the TiO2 powder is m(TiO2), and the mass of SiO2 in the silicon source is m(SiO2), wherein m(TiO2) / [m(TiO2)+m(SiO2)] = 2.5%~10%; and / or, The stirring time is 0.1~60 min; and / or, The power of the ultrasound is 100~300 W; and / or, The ultrasound session lasts 1 to 5 minutes.
[0011] In some embodiments, in step S40, the gelation treatment includes gelation using a fiber felt pad, wherein: The fiber felt is any one of high silica fiber, quartz fiber, aluminum silicate fiber, alumina fiber, or mullite fiber.
[0012] In some embodiments, the aging temperature is 30~70°C; and / or the aging time is 2~12h.
[0013] In some implementations, in step S50, The second acidic solution comprises one or more of hydrochloric acid, hydrofluoric acid, hydrobromic acid, sulfuric acid, phosphoric acid, nitric acid, oxalic acid, glacial acetic acid, and p-toluenesulfonic acid, preferably p-toluenesulfonic acid; and / or, The concentration of the second acidic solution is 0.01~32.5 mol / L.
[0014] In some implementations, in step S50, The solvent replacement temperature is 40~80℃; and / or, The solvent replacement time is 4-12 hours; and / or, The surface modification treatment uses one or more of the following modifiers: methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, trimethylchlorosilane, phenyltriethoxysilane, dimethyldichlorosilane, trimethylethoxysilane, trimethylbromosilane, trimethoxysilane, tetramethylsilane, dimethyldimethoxysilane, dimethyldiethoxysilane, hexamethyldisiloxane, bis(trimethylsilyl)acetamide, and hexamethyldisilazane; and / or, The surface modification treatment is performed at a temperature of 60~150℃; and / or, The surface modification treatment takes 1 to 6 hours; and / or, The drying temperature is 80~200℃; and / or, The drying time is 2 to 12 hours.
[0015] This application provides an aerogel composite material, which is prepared by any one of the aerogel composite materials described above.
[0016] This application discloses a method for preparing an aerogel composite material. The aerogel composite material uses titanium dioxide as a light-blocking agent, which can inhibit infrared radiation heat transfer, reduce the thermal conductivity of the aerogel at high temperatures, and thus reduce its calorific value. This avoids the potential fire risk caused by the combustion and pyrolysis of pure silica aerogel at high temperatures, while maintaining its excellent basic properties such as low density, low thermal conductivity, high porosity, and high specific surface area, thus promoting the application of silica aerogel composite materials in the field of high-temperature thermal insulation. Attached Figure Description
[0017] Figure 1 This is a schematic diagram showing the changes in calorific value (GCV) and thermal conductivity of the aerogel composite materials prepared in Examples 1-4 and Comparative Example 1 of this application; Figure 2 This is a schematic TG image of the SiO2 aerogel composite material without TiO2 doping in Comparative Example 1 of this application; Figure 3 This is a schematic diagram of the TG image of TiO2 / SiO2-2.5% in Example 1 of this application; Figure 4 This is a schematic diagram of the TG image of TiO2 / SiO2-5% in Example 2 of this application; Figure 5 This is a schematic diagram of the TG image of TiO2 / SiO2-7.5% in Example 3 of this application; Figure 6 This is a schematic diagram of the TG image of TiO2 / SiO2-10% in Example 4 of this application; Figure 7 This is a schematic diagram showing the change in thermal conductivity of the SiO2 aerogel composite material without TiO2 doping in Comparative Example 1 of this application at different temperatures. Figure 8 This is a schematic diagram showing the change curves of the thermal conductivity of TiO2 / SiO2-10% at different temperatures in Example 4 of this application; Figure 9 This is a schematic diagram showing the infrared transmittance variation curves of the TiO2 / SiO2-2.5%, TiO2 / SiO2-5%, TiO2 / SiO2-7.5%, TiO2 / SiO2-10% TiO2 / SiO2 aerogel composite materials in Examples 1-4 of this application and the undoped TiO2 SiO2 aerogel composite material in Comparative Example 1. Figure 10 This is a schematic diagram showing the specific extinction coefficient variation curves of the TiO2 / SiO2-2.5%, TiO2 / SiO2-5%, TiO2 / SiO2-7.5%, TiO2 / SiO2-10% TiO2 / SiO2 aerogel composite materials in Examples 1-4 of this application and the undoped TiO2 SiO2 aerogel composite material in Comparative Example 1. Figure 11 This is a schematic SEM image of the SiO2 aerogel composite material without TiO2 doping in Comparative Example 1 of this application. Figure 12 This is a schematic SEM image of TiO2 / SiO2-2.5% in Example 1 of this application; Figure 13 This is a schematic SEM image of TiO2 / SiO2-5% in Example 2 of this application; Figure 14 This is a schematic SEM image of TiO2 / SiO2-7.5% in Example 3 of this application; Figure 15 This is a schematic SEM image of TiO2 / SiO2-10% in Example 4 of this application. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially. Furthermore, the meaning of "and / or" throughout the text includes three parallel solutions; for example, "A and / or B" includes solution A, or solution B, or a solution where both A and B are satisfied simultaneously. In addition, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] Currently, at higher temperatures (200~500℃), the pyrolysis of organic groups in silica aerogels can destroy their structural integrity, causing the skeleton to collapse and shrink. At the same time, at even higher temperatures (500~1000℃), the high infrared transparency of silica aerogels enhances their infrared radiation heat transfer at high temperatures, increasing the high-temperature thermal conductivity of the aerogels and bringing unnecessary potential thermal hazards. Therefore, the combustion pyrolysis of silica aerogels at high temperatures has become a crucial issue and challenge in their application.
[0020] In view of the above, this application provides a method for preparing an aerogel composite material, comprising the following steps: S10. Mix and dilute the silicon source with the aqueous solution to obtain a diluted solution; S20. The diluted solution is mixed with the first acidic solution and subjected to acidification treatment to obtain a sol solution; S30. The sol solution is stirred and mixed with TiO2 powder, and then subjected to ultrasonic treatment to obtain a TiO2 / SiO2 mixed sol solution; S40. The TiO2 / SiO2 mixed sol solution is subjected to gelation treatment and aging to obtain TiO2 / SiO2 wet gel composite material. S50. The TiO2 / SiO2 wet gel composite material is mixed with a second acidic solution, solvent replacement is performed, surface modification treatment is carried out, and then it is dried to obtain an aerogel composite material.
[0021] This application discloses a method for preparing an aerogel composite material and its application. The aerogel composite material uses titanium dioxide as a light-blocking agent, which can inhibit infrared radiation heat transfer, reduce the thermal conductivity of the aerogel at high temperatures, and thus reduce its calorific value. This avoids the potential fire risk caused by the pyrolysis of pure silica aerogel at high temperatures, while maintaining its excellent basic properties such as low density, low thermal conductivity, high porosity, and high specific surface area, thus promoting the application of silica aerogel composite materials in the field of high-temperature insulation.
[0022] It should be noted that this invention fully considers the inhibitory effect of titanium dioxide on infrared radiation heat transfer and applies it to the preparation process of low-calorific-value silica aerogels. This compensates for the lack of high infrared transparency of silica aerogels at high temperatures, reduces the high-temperature thermal conductivity of the aerogel, and thus effectively reduces its calorific value, decreasing the possibility of fire caused by unavoidable high temperatures, flames, or heat radiation from ignition of other materials. Furthermore, compared to other methods for improving the combustion characteristics of silica aerogels, the introduced titanium dioxide does not undergo thermal decomposition or other side reactions during combustion; it only undergoes a crystal form change, transforming from perovskite to rutile. It is also less prone to oxidation and failure at high temperatures. The titanium dioxide-doped aerogel can be prepared by atmospheric pressure drying, requiring no complex processes, making it economical and environmentally friendly. Finally, the prepared silica aerogel maintains its low density (0.2~0.4 g / cm³). 3 The excellent properties of silica aerogel, such as low thermal conductivity (0.016~0.018 W / m·K), ensure its superior thermal insulation performance. This overcomes the drawback that the introduction of light-blocking agents / flame retardants would have an adverse effect on the thermal insulation performance of aerogel, thus promoting the application of silica aerogel in the field of high-temperature thermal insulation.
[0023] Furthermore, this invention improves the existing atmospheric pressure preparation process of titanium dioxide-doped silica aerogels. In the surface modification stage, a high-pressure reactor can be used, which can increase the modification temperature to 120~150℃ compared with the traditional water bath heating modification. At the same time, a lower pressure level (0~2MPa) can be maintained in the container, thereby greatly shortening the preparation cycle of aerogels. The entire preparation process takes no more than 2 days, and the operation is simple, convenient, safe and reliable, which is more conducive to industrial production.
[0024] In some embodiments, in step S10, the silicon source includes an organosilicon source and an inorganic silicon source; the organosilicon source includes one or more of tetraethyl orthosilicate, tetramethyl orthosilicate, tetrabutyl orthosilicate, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, polysiloxane, 3-[2-(2-aminoethylamino)ethylamino]propyltrimethoxysilane, and n-octyltriethoxysilane; the inorganic silicon source includes... The aerogel contains one or more of water glass and silicon tetrachloride. Specifically, the polysiloxane is polydimethylsiloxane or polydiethylsiloxane. These substances can be used to provide a silicon source, and the choice of silicon source affects the pore structure and specific surface area of the aerogel. Therefore, the preferred mass fraction of the water glass solution is 26-46%, and the modulus is 2.1-4.8. This is because water glass, as an inexpensive industrial-grade raw material, has advantages over organosilicon sources such as tetraethyl orthosilicate (TEOS) in terms of low cost (cost can be reduced by tens of times), readily available raw materials, non-toxicity, environmental friendliness, and fewer reaction byproducts. In addition, a higher silicon-to-water ratio is beneficial for forming a denser pore structure, but an excessively high silicon-to-water ratio can lead to particle aggregation. Specifically, this invention prefers a water glass solution with a silicon-to-water ratio of 1:4 as the silicon source.
[0025] Furthermore, an alcohol solution may be added in step S10. The alcohol solution includes one or more of methanol, ethanol, propanol, isopropanol, butanol, isobutanol, ethylene glycol, propylene glycol, diethylene glycol, butanediol, diacetone alcohol, glycerol, and diethylene glycol. The above alcohol solution can be used as a solvent in the organosilicon source sol-gel stage to dissolve the precursor of silica. The hydrolysate of the water glass solution can be deionized water only.
[0026] In some embodiments, in step S20, the first acidic solution includes one or more of hydrochloric acid, hydrofluoric acid, hydrobromic acid, sulfuric acid, phosphoric acid, nitric acid, oxalic acid, and glacial acetic acid. The above acids are mainly used for acidification treatment. The concentration of the first acidic solution is 0.01~29.8 mol / L. Within this concentration range, the effect is better.
[0027] Furthermore, the acidification treatment temperature is 10~70℃; and / or the acidification treatment time is 0.1~50min. Under these acidification conditions, the hydrolysis and gelation reaction of the silicon source can be catalyzed, promoting the hydrolysis of the silicon source to form silanol and causing a gel polymerization reaction, thereby forming a three-dimensional network structure of aerogel.
[0028] In some embodiments, in step S20, the volume ratio of the diluent to the first acidic solution is (1~24):1, specifically, it can be 1:1, 15:1, 20:1 or 24:1. Within this range, acidification can be sufficient.
[0029] In some embodiments, in step S30, the average particle size of the TiO2 powder ranges from 0.1 to 3 μm. TiO2 particles within this range have good scattering efficiency for visible and infrared light, effectively blocking radiative heat transfer. If the particle size is too small (e.g., nanometer-scale), it is prone to agglomeration leading to uneven dispersion; if the particle size is too large, it may damage the porous structure of the aerogel, affecting its lightweight properties. Simultaneously, TiO2 particles within this particle size range are more easily and uniformly distributed in the silica aerogel matrix through ultrasonic dispersion during the sol-gel process, avoiding localized stress concentration or pore structure collapse caused by particle aggregation.
[0030] In some embodiments, the mass of the TiO2 powder is m(TiO2), and the mass of SiO2 in the silicon source is m(SiO2), wherein m(TiO2) / [m(TiO2)+m(SiO2)]=2.5%~10%, within this range, because at this amount of addition, the aerogel can maintain its excellent intrinsic properties such as low density and low thermal conductivity.
[0031] Specifically, the amount of TiO2 powder added is determined as follows: The mass m(SiO2) of SiO2 in the silicon source is calculated based on the concentration and amount of silicon source used; then, the required mass m(TiO2) of TiO2 powder is calculated based on the target mass fraction, such that m(TiO2) / [m(TiO2)+m(SiO2)] equals the target mass fraction. For example, when the target mass fraction is 2.5%, m(TiO2) / [m(TiO2)+m(SiO2)] = 2.5%.
[0032] In some embodiments, in step S30, the solute in the alkaline aqueous solution includes one or more of ammonia, sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium carbonate, or sodium silicate. Furthermore, the concentration of the alkaline aqueous solution is 0.01~8 mol / L, and the alkaline aqueous solution is used to adjust the pH value of the sol solution to 3~9.
[0033] To ensure uniform mixing of micron-sized titanium dioxide and nano-sized silica aerogel, the stirring time in this embodiment is 0.1~60 min, the ultrasonic power is 100~300 W, and the ultrasonic time is 1~5 min. Since there is a size difference between micron-sized titanium dioxide and nano-sized aerogel, ultrasonic treatment is required during the sol-gel process to ensure uniform dispersion of titanium dioxide particles in the aerogel, thereby enhancing the physical bonding between materials and optimizing the pore structure of the composite material.
[0034] In some embodiments, in step S50, the fiber mat is any one of high silica fiber, quartz fiber, aluminosilicate fiber, alumina fiber and mullite fiber. The fiber mat can form a mechanical support framework through a three-dimensional interwoven structure, which can stabilize the multi-level pore morphology of the composite material and suppress structural deformation, and can also realize the non-destructive transfer and directional processing of aerogel composite materials in subsequent processes.
[0035] In some embodiments, the aging temperature is 30~70°C; and / or the aging time is 2~12h. Within this aging range, the mechanical properties of the prepared TiO2 / SiO2 wet gel composite material are improved, and the flame retardant properties can be further improved.
[0036] In some embodiments, in step S50, the second acidic solution includes one or more of hydrochloric acid, hydrofluoric acid, hydrobromic acid, sulfuric acid, phosphoric acid, nitric acid, oxalic acid, glacial acetic acid, and p-toluenesulfonic acid, preferably p-toluenesulfonic acid. In the surface treatment, p-toluenesulfonic acid is specifically used for catalytic modification. Using p-toluenesulfonic acid organic acid for modification can give the aerogel better performance.
[0037] Furthermore, the concentration of the second acidic solution is 0.01~32.5 mol / L, and the heat insulation effect is better within this range.
[0038] In some embodiments, the solvent replacement temperature is 40~80°C; and / or the solvent replacement time is 4~12h. Within this range, the purpose of solvent replacement is to remove residual moisture and reaction byproducts inside the wet gel composite material, avoid competition between the hydrophobic modifier and water during subsequent surface modification treatment, and ensure that hydrophobic groups (such as methyl groups) effectively replace the hydrophilic hydroxyl groups (-OH) on the gel surface to form a stable hydrophobic layer.
[0039] The surface modification process is carried out in a high-pressure hydrothermal autoclave. Compared with traditional heating modification, the hydrothermal modification method used in this application has a wider range of temperature and pressure control, and the pressure environment formed can improve the efficiency and effect of aerogel modification.
[0040] The surface modification treatment uses one or more of the following modifiers: methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, trimethylchlorosilane, phenyltriethoxysilane, dimethyldichlorosilane, trimethylethoxysilane, trimethylbromosilane, trimethoxysilane, tetramethylsilane, dimethyldimethoxysilane, dimethyldiethoxysilane, hexamethyldisiloxane, bis(trimethylsilyl)acetamide, and hexamethyldisilazane. The purpose of using the above modifiers is to replace the silanol groups on the aerogel surface with hydrophobic organic groups, reduce the capillary force on the aerogel surface, prevent the collapse of the pore structure during normal pressure drying, and at the same time enhance the hydrophobicity of the material and extend its service life.
[0041] The surface modification treatment temperature is 80~120℃, which can be 80℃, 90℃, 100℃ or 120℃. Compared with room temperature, it can increase the reaction rate and shorten the reaction time. The surface modification treatment time is correspondingly shortened to 1~6 hours.
[0042] The drying temperature is 80~200℃; and / or the drying time is 2~12h. Within this range of surface modification treatment and drying time, the hydrophobic modification reaction can be fully carried out, while avoiding excessive thermal stress damage during the drying process, thereby maintaining the structural integrity and functional stability of the aerogel composite material.
[0043] This application provides an aerogel composite material, which is prepared by any one of the aerogel composite materials described above.
[0044] The aerogel composite material proposed in this application possesses all the excellent effects of the above-mentioned aerogel composite material preparation methods, which will not be elaborated here.
[0045] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0046] Example 1 This invention provides a method for preparing an aerogel composite material, comprising the following steps: S10. Preparation of diluted water glass solution: Take sodium silicate aqueous solution (water glass, modulus M = 3.3, SiO2 content 28.5 wt%, Na2O content 8.8 wt%) and deionized water at a volume ratio of 1:4, stir evenly to obtain diluted water glass solution.
[0047] S20. Mix the above diluted water glass solution with 70% sulfuric acid solution at a volume ratio of 20:3 and stir on a magnetic stirrer to obtain a sol solution.
[0048] S30. Before gel formation, add 2.5% (i.e., the amount of TiO2 added is based on the mass of TiO2 in the final product being 2.5% of the total mass of TiO2 and SiO2) of TiO2 powder to the above sol solution. The TiO2 is uniformly dispersed in the silica sol by mechanical stirring for 50 min and ultrasonic dispersion (power 300W, time 5 min) to obtain TiO2 / SiO2 mixed sol.
[0049] S40. The above TiO2 / SiO2 mixed sol is poured into a glass fiber felt pad and allowed to stand for about 15 minutes to gel. Then, it is allowed to stand and age at room temperature for 10 hours to obtain a TiO2 / SiO2 wet gel composite material.
[0050] S50. Solvent Replacement: The above TiO2 / SiO2 wet gel composite material was placed in a mixture of ethanol, deionized water, and 70% sulfuric acid for solvent replacement, wherein the volume ratio of ethanol, deionized water, and 70% sulfuric acid was 50:48:12. After the first replacement for 6 hours, the replacement solution was poured off, and the same mixture was added for a second replacement for 6 hours to complete the solvent replacement process. After solvent replacement, hexamethyldisilazane (HMDS) was added to the wet gel composite material, so that the HMDS liquid level was about 1 cm above the gel surface. The mixture was then placed in a reaction vessel and subjected to hydrophobic modification at 100 °C for 2 hours. After modification, the hydrophobic TiO2 / SiO2 wet gel composite material was removed and placed in a forced-air drying oven at 120 °C for 4 hours to obtain a TiO2 / SiO2 aerogel composite material dried at atmospheric pressure.
[0051] Example 2 Except for the TiO2 mass fraction of 5%, the other preparation processes are the same as in Example 1.
[0052] Example 3 Except for the TiO2 mass fraction of 7.5%, the other preparation processes are the same as in Example 1.
[0053] Example 4 Except for the TiO2 mass fraction of 10%, the other preparation processes are the same as in Example 1.
[0054] Comparative Example 1 Without adding TiO2, the other preparation processes are the same as in Example 1, yielding an aerogel composite material.
[0055] Performance testing Thermal conductivity: The sample to be tested is placed in a sealed container (oxygen bomb) filled with high-pressure oxygen and completely burned. The heat released by combustion is absorbed by the water in the inner cylinder of the calorimeter. By measuring the rise in water temperature and combining it with the instrument's heat capacity (water equivalent), the total calorific value of the sample is calculated, referring to GB / T 14402-2007 "Determination of calorific value of combustion of building materials and products".
[0056] Thermal stability: Thermogravimetric analysis (TGA) involves placing the sample in a thermogravimetric analyzer and heating it at a constant heating rate under programmed temperature control, recording the change in sample mass with temperature in real time.
[0057] Contact angle: The static water contact angle was determined using the seated drop method. A contact angle measuring instrument was used, the test liquid was ultrapure water, the droplet volume was 2 μL, and the test was performed 5 times at different positions on the sample surface and the average value was taken. The test environment temperature was 23±2℃.
[0058] Total calorific value: Refer to the test method in GB / T 14402-2007.
[0059] The test results of the above embodiments and comparative examples are as follows: Among them, the test results of thermal conductivity and total flammability are as follows: Figure 1 As shown in Table 1: Table 1
[0060] As shown in Table 1, compared with Comparative Example 1, the thermal conductivity of the TiO2 / SiO2 aerogel composite materials provided in Examples 1 to 4 remains at a low level, while maintaining excellent hydrophobic properties.
[0061] from Figure 1 As can be seen, the TiO2 / SiO2 composite materials provided in Examples 1-4 still maintain an ultra-low thermal conductivity of less than 0.020 W / (m·K), indicating that the introduction of TiO2 can reduce its calorific value without damage while maintaining the excellent thermal insulation performance of the aerogel. This is also true for the aerogel composite materials provided in Examples 1-4 and Comparative Example 1. The introduction of TiO2 significantly reduces the calorific value of the aerogel composite material, demonstrating that the introduction of TiO2 can effectively reduce the thermal hazards of hydrophobic silica aerogel and improve its thermal stability at high temperatures. Here, GCV is an abbreviation for Gross Calorific Value.
[0062] from Figures 2-6 As can be seen from the image, SA in the picture is SiO2. Figure 2 For example, the gray curve is the TG (thermogravimetric) curve, and the vertical axis is the mass percentage (%), reflecting the mass loss of the sample as the temperature increases; The black curve is the DSC (Differential Scanning Calorimetry) curve, with the vertical axis representing heat flow (W / g), reflecting the heat absorbed or released by the sample during heating. This TiO2 / SA-2.5% composite material begins to lose weight at approximately 390℃, reaching its maximum weight loss rate around 400℃, indicating that its main thermal decomposition or structural damage occurs within this temperature range. The other figures are similar. In the TG-DSC curves for TiO2 / SiO2 ratios of 2.5%, 5%, 7.5%, and 10%, the initial decomposition temperature and peak heat release rate of the aerogel gradually increase with increasing titanium dioxide doping content. This fully demonstrates the inhibitory effect of the light-shielding agent TiO2 on the thermal decomposition process of the aerogel. With higher TiO2 content, the composite aerogel has a higher thermal decomposition temperature. At higher temperatures (500~1000℃), the high infrared transparency of silica aerogel enhances its infrared radiation heat transfer at high temperatures. The addition of TiO2 can fully compensate for the increase in thermal conductivity at high temperatures, delay its thermal decomposition at high temperatures, increase the thermal decomposition temperature, reduce the heat release, and thus reduce its calorific value, thereby significantly improving the thermal stability of silica aerogel at high temperatures.
[0063] in, Figure 2 For Comparative Example 1, without TiO2 doping, Figures 7-8 The figures show the high-temperature thermal conductivity curves of the undoped SiO2 silica aerogel in Comparative Example 1 and the TiO2 / SiO2-10% aerogel in the examples. As can be seen from the figures, the thermal conductivity of the SiO2 aerogel increases sharply above 300℃, reaching over 0.050 W / (m·K) at 60℃. In contrast, the thermal conductivity of TiO2 / SiO2-10% at 600℃ is only 0.0255 W / (m·K), even lower than that of air. This clearly demonstrates that TiO2 doping can effectively suppress the high-temperature heat conduction process of silica, improve its high-temperature thermal stability, and thus suppress its risk of pyrolysis and combustion at high temperatures.
[0064] Figures 9-10 The figures show the infrared transmittance and mass-to-mass extinction coefficient variations of the undoped silica aerogel in Comparative Example 1 and the TiO2 / SiO2-2.5%, TiO2 / SiO2-5%, TiO2 / SiO2-7.5%, and TiO2 / SiO2-10% aerogels in Examples 1-4, respectively. As can be seen from the figures, the infrared transmittance of the silica aerogel significantly decreases while the mass-to-mass extinction coefficient significantly increases after TiO2 doping, and this coefficient changes monotonically with increasing TiO2 doping concentration. This fully demonstrates the inhibitory effect of TiO2 on the high-temperature infrared radiation heat transfer of the silica aerogel composite material.
[0065] Figures 11-15The SEM images obtained are as follows: Comparative Example 1: Undoped TiO2 silica aerogel; and Examples 1-4: TiO2 / SiO2-2.5%, TiO2 / SiO2-5%, TiO2 / SiO2-7.5%, and TiO2 / SiO2-10%. The images show that the microstructure of the TiO2 / SiO2 composite material is similar to that of pure silica aerogel, both consisting of a three-dimensional nanoporous network composed of secondary silica nanoparticles.
[0066] The above are merely preferred embodiments of this application and do not limit the patent scope of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the patent protection scope of this application.
Claims
1. A method for preparing an aerogel composite material, characterized in that, Includes the following steps: S10. Mix and dilute the silicon source with the aqueous solution to obtain a diluted solution; S20. The diluted solution is mixed with the first acidic solution and subjected to acidification treatment to obtain a sol solution; S30. The sol solution is stirred and mixed with TiO2 powder, and then subjected to ultrasonic treatment to obtain a TiO2 / SiO2 mixed sol solution; S40. The TiO2 / SiO2 mixed sol solution is subjected to gelation treatment and aging to obtain TiO2 / SiO2 wet gel composite material. S50. The TiO2 / SiO2 wet gel composite material is mixed with a second acidic solution, solvent replacement is performed, surface modification treatment is carried out, and then it is dried to obtain an aerogel composite material.
2. The method for preparing the aerogel composite material as described in claim 1, characterized in that, In step S10, the silicon source includes an organosilicon source and an inorganic silicon source: The organosilicon source includes one or more of tetraethyl orthosilicate, tetramethyl orthosilicate, tetrabutyl orthosilicate, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, polysiloxane, 3-[2-(2-aminoethylamino)ethylamino]propyltrimethoxysilane, and n-octyltriethoxysilane; and / or, The inorganic silicon source includes one or more of water glass and silicon tetrachloride; and / or, The alcohol solution includes one or more of methanol, ethanol, propanol, isopropanol, butanol, isobutanol, ethylene glycol, propylene glycol, diethylene glycol, butanediol, diacetone alcohol, glycerol, and diethylene glycol.
3. The method for preparing the aerogel composite material as described in claim 1, characterized in that, In step S20, the first acidic solution includes one or more of hydrochloric acid, hydrofluoric acid, hydrobromic acid, sulfuric acid, phosphoric acid, nitric acid, oxalic acid, and glacial acetic acid; and / or, The concentration of the first acidic solution is 0.01~29.8 mol / L; and / or, The acidification treatment temperature is 10~70℃; and / or, The acidification treatment time is 0.1~50 min.
4. The method for preparing the aerogel composite material as described in claim 1, characterized in that, In step S20, the volume ratio of the diluent to the first acidic solution is (1~24):
1.
5. The method for preparing the aerogel composite material as described in claim 1, characterized in that, In step S30, the average particle size of the TiO2 powder ranges from 0.1 to 3 μm; and / or, The mass of the TiO2 powder is m(TiO2), and the mass of SiO2 in the silicon source is m(SiO2), wherein m(TiO2) / [m(TiO2)+m(SiO2)] = 2.5%~10%; and / or, The stirring time is 0.1~60 min; and / or, The power of the ultrasound is 100~300 W; and / or, The ultrasound session lasts 1 to 5 minutes.
6. The method for preparing the aerogel composite material as described in claim 1, characterized in that, In step S40, the gelation process includes gelation using a fiber felt pad, wherein: The fiber felt pad includes at least one of high silica fiber, quartz fiber, aluminum silicate fiber, alumina fiber, and mullite fiber.
7. The method for preparing the aerogel composite material according to claim 1, characterized in that, The aging temperature is 30~70℃; and / or, The aging time is 2~12 hours.
8. The method for preparing the aerogel composite material as described in claim 1, characterized in that, In step S50, The second acidic solution includes one or more of hydrochloric acid, hydrofluoric acid, hydrobromic acid, sulfuric acid, phosphoric acid, nitric acid, oxalic acid, glacial acetic acid, and p-toluenesulfonic acid; and / or, The concentration of the second acidic solution is 0.01~32.5 mol / L.
9. The method for preparing the aerogel composite material as described in claim 1, characterized in that, In step S50, The solvent replacement temperature is 40~80℃; and / or, The solvent replacement time is 4-12 hours; and / or, The surface modification treatment uses one or more of the following modifiers: methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, trimethylchlorosilane, phenyltriethoxysilane, dimethyldichlorosilane, trimethylethoxysilane, trimethylbromosilane, trimethoxysilane, tetramethylsilane, dimethyldimethoxysilane, dimethyldiethoxysilane, hexamethyldisiloxane, bis(trimethylsilyl)acetamide, and hexamethyldisilazane; and / or, The surface modification treatment is performed at a temperature of 80~120℃; and / or, The surface modification treatment takes 1 to 6 hours; and / or, The drying temperature is 80~200℃; and / or, The drying time is 2 to 12 hours.
10. An aerogel composite material, characterized in that, The aerogel composite material is prepared by the method described in any one of claims 1 to 9.